2015
DOI: 10.1094/pdis-03-14-0327-re
|View full text |Cite
|
Sign up to set email alerts
|

A Postharvest Fruit Rot of Apple Caused by Lambertella corni-maris in Washington State

Abstract: Wiseman, M. S., Dugan, F. M., Kim, Y. K., and Xiao, C. L. 2015. A postharvest fruit rot of apple caused by Lambertella corni-maris in Washington State. Plant Dis. 99:201-206.During surveys for postharvest diseases of apple conducted in Wash ington State, an unknown fruit rot was observed on stored apple fruit collected from commercial fruit packinghouses. This disease was pre sent in 66 of the 179 grower lots sampled, accounting for an average 1 to 3% of the total decayed fruit sampled. The disease appeared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Previous studies have reported Lambertella on various substrates, such as rotten or mummi ed fruits (Wiseman et al, 2015), and dead twigs and leaves (Tewari & Pant, 1967). Geographically, Lambertella has been found in various regions in the tropics, northern and southern hemispheres (Whetzel, 1943;Cash, 1958;Tewari, 1963;Dumont, 1971;Dumont, 1974 2016), even though phylogenetic positions for some species, such as L. pruni that showed slight differences in our phylogram based on ITS and LSU sequence data and with more Lambertella species and other representative genera in Rutstroemiaceae (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported Lambertella on various substrates, such as rotten or mummi ed fruits (Wiseman et al, 2015), and dead twigs and leaves (Tewari & Pant, 1967). Geographically, Lambertella has been found in various regions in the tropics, northern and southern hemispheres (Whetzel, 1943;Cash, 1958;Tewari, 1963;Dumont, 1971;Dumont, 1974 2016), even though phylogenetic positions for some species, such as L. pruni that showed slight differences in our phylogram based on ITS and LSU sequence data and with more Lambertella species and other representative genera in Rutstroemiaceae (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The family was characterized by brownish and greenish, stipitate to substipitate apothecia or sometimes cleistothecia with inoperculate, cylindric-clavate asci, and hyaline to brown, fusiform to ellipsoid ascospores. It mainly includes saprobes and a few parasites (Holst-Jensen et al, 1997; Galán et al, 2015;Wiseman et al, 2015;Zhao et al, 2016;Baral, 2017;Johnston et al, 2019). With several taxonomic revisions camera for photographs while Tarosoft (R) Image Frame Work software was used for the measurement (Senanayake et al 2020).…”
Section: Introductionmentioning
confidence: 99%